Adipose Tissue and Adipokines in Health and Disease - Fantuzzi, Giamila; Braunschweig, Carol (Nutrition and Health,, 2014)
The field of adipose tissue biology has been expanding at a very rapid pace in the last few years. Numerous advances have been made since publication of the first edition of this book, in terms of basic adipocyte biology, understanding of the determinants of obesity, distribution of body fat and weight loss, as well as the mechanisms linking excess adiposity to various co-morbidities. Adipose Tissue and Adipokines in Health and Disease, Second Edition contains updated chapters from the previous volume but as the field has evolved, some areas covered in the first edition have been refocused to address the new knowledge. The volume is divided in four sections: the first two deal with basic adipose tissue and adipokine biology, while the last two address the problem of obesity and alterations in adipose tissue function from an epidemiological and clinical standpoint. The chapters are written by experts in their fields and include the most up to date scientific information. Adipose Tissue and Adipokines in Health and Disease, Second Edition is a useful resource for physicians interested in adipose tissue biology and basic scientists who want to know more about applied aspects of the field. The book targets endocrinologists, residents and fellows, internists, nutritionists and general practitioners who are exposed to an ever-expanding obese population.